2017
DOI: 10.1111/mmi.13729
|View full text |Cite
|
Sign up to set email alerts
|

Not a barrier but a key: How bacteriophages exploit host's O‐antigen as an essential receptor to initiate infection

Abstract: Summary Tailed bacteriophages specific for Gram‐negative bacteria encounter lipopolysaccharide (LPS) during the first infection steps. Yet, it is not well understood how biochemistry of these initial interactions relates to subsequent events that orchestrate phage adsorption and tail rearrangements to initiate cell entry. For many phages, long O‐antigen chains found on the LPS of smooth bacterial strains serve as essential receptor recognized by their tailspike proteins (TSP). Many TSP are depolymerases and O‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 33 publications
0
91
0
Order By: Relevance
“…For example, we used two laboratory E. coli strains that have rough LPS architecture where core oligosaccharide is the terminal part of the LPS. However, it is known that the genetic and structural diversity of LPS and the repeat structure O-polysaccharide attached to LPS (to form smooth LPS) is very large in pathogenic and environmental isolates of Enterobacteriaceae, and may impact phage infectivity [47,57,[199][200][201][202]. The genetic screens presented in this work may aid in filling the knowledge gap on phage interaction with different O-antigens and its impact on phage infectivity and resistance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, we used two laboratory E. coli strains that have rough LPS architecture where core oligosaccharide is the terminal part of the LPS. However, it is known that the genetic and structural diversity of LPS and the repeat structure O-polysaccharide attached to LPS (to form smooth LPS) is very large in pathogenic and environmental isolates of Enterobacteriaceae, and may impact phage infectivity [47,57,[199][200][201][202]. The genetic screens presented in this work may aid in filling the knowledge gap on phage interaction with different O-antigens and its impact on phage infectivity and resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Bacterial sensitivity/resistance to phages is typically characterized using phenotypic methods such as cross-infection patterns against a panel of phages [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or by whole-genome sequencing of phage-resistant mutants [28][29][30][31][32]. As such, our understanding of bacterial resistance mechanisms against phages remains limited, and the field is therefore in need of improved methods to characterize phage-host interactions, determine the generality and diversity of phage resistance mechanisms in nature, and identify the degree of specificity for each bacterial resistance mechanism across diverse phage types [13,25,26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, as previous reports have shown that LPS is critical for P22 entry (Liu et al ., ). LPS has also been shown to contribute to particle ejection in vitro (Andres et al ., ); recently reviewed in (Broeker and Barbirz, ). However, LPS causes a slow and inefficient triggering of P22 ejection alone, whereas outer membrane proteins are critical for accelerating this process and for E‐protein release, which is essential for infection (Jin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In their functional context, bacteriophage TSPs are indispensable tail parts rendering the maturep hage into an efficient, multivalent particlef or adsorption to ab acterial surfacet os tart infection. [74,75] Multivalent binding observed for Sf6TSPo nt he activated SfY polysaccharide surface resembles the interactions of Sf6 bacteriophage with LPS covered S. flexneri surfaces. Here, the typical bimodal O-polysaccharidec hain length distribution found in S. flexneri LPS resultsi naheterogeneous glycan ligand surface.…”
Section: Discussionmentioning
confidence: 99%